A Method for Evaluating Three-Dimensional Morphological Features: A Case Study Using Marchantia polymorpha - Furuya, Tomoyuki; Kimori, Yoshitaka; Tsukaya, Hirokazu (Frontiers in Plant Science, 2019)
The description and evaluation of morphological features are essential to many biological studies. Bioimaging and quantification methods have been developed to analyze the morphological features of plants. However, efficient three-dimensional (3D) imaging and its quantification are still under development, particularly for studies of plant morphology, due to complex organ structure with great flexibility among individuals with the same genotype. In this study, we propose a new approach that combines a 3D imaging technique using micro-computed tomography and a mathematical image-processing method to describe 3D morphological features. As an example, we applied this method to Marchantia polymorpha, a new model plant used for the evolutional study of land plants, and evaluated a mutant individual with an abnormal 3D shape. Using this new method, we quantitatively described the thallus morphology of M. polymorpha and distinguished the wild type from a mutant with different morphological features. Our newly established method can be applied to various tissues or bodies with irregular 3D morphology. or bodies with irregular 3D morphology.